The Silent Message We Send to Future Bioethicists - Salem, Nada (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2026)
Many bioethicists do not consider advocacy to be part of their role despite the longstanding relationship between health research and the sociopolitical forces that shape it. As a Canadian graduate student in the United States, I reflect on the unique experience of studying bioethics at a time of declining funding in health research and a dominating culture of academic suppression. I discuss the passive lessons that students are learning from the actions (or lack thereof) of bioethicists, and why expressing solidarity with other affected groups can strengthen our academic community, pointing to examples of what these advocacy efforts can look like.